Military Families Coping with Death, Dying and Grief Issues - Nichols, Quienton; Williams, Molly N. (Advances in Social Sciences Research Journal, 2017)
There has been approximately 1.5 million service members who have spent service time in Iraq, of which about 500,000 have served two tours of combat (Whitlock, 2008 as cited by Huebner, Mancini, Bowen, & Orthner, 2009). Given that deployment tours can last up to 15 months, many military personnel have been spending more time overseas than at home. As the Global War on Terrorism (GWOT) continues the death rate continues to rise, there are many families and children that will have to cope with the death of a love one and the grief that comes with it. This article will bring awareness to helping professionals and agencies that work with military families and their relatives after the death of a service member. It will show the length and use of such modalities as the social learning theory and the grief cycle model in offering the best interventions and techniques when providing psychological services to families of services members who died while in combat. It will also provide a starting point and mid-point for love ones that may be seeking additional resources after the death of a family member.